A Role for B Cells to Transmit Hepatitis C Virus Infection - Desombere, Isabelle; Van Houtte, Freya; Farhoudi, Ali; Verhoye, Lieven; Buysschaert, Caroline; Gijbels, Yvonne; Couvent, Sibyl; Swinnen, Wilfried; Van Vlierberghe, Hans; Elewaut, André; Magri, Andrea; Stamataki, Zania; et al. (Frontiers in Immunology, 2021)
Hepatitis C virus (HCV) is highly variable and transmits through infected blood to establish a chronic liver infection in the majority of patients. Our knowledge on the infectivity of clinical HCV strains is hampered by the lack of in vitro cell culture systems that support efficient viral replication. We and others have reported that HCV can associate with and infect immune cells and may thereby evade host immune surveillance and elimination. To evaluate whether B cells play a role in HCV transmission, we assessed the ability of B cells and sera from recent (<2 years) or chronic (≥ 2 years) HCV patients to infect humanized liver chimeric mice. HCV was transmitted by B cells from chronic infected patients whereas the sera were non-infectious. In contrast, B cells from recently infected patients failed to transmit HCV to the mice, whereas all serum samples were infectious. We observed an association between circulating anti-glycoprotein E1E2 antibodies and B cell HCV transmission. Taken together, our studies provide evidence for HCV transmission by B cells, findings that have clinical implications for prophylactic and therapeutic antibody-based vaccine design.